Way of Umm Abbas (1867) Historical study (Journal of the College of Basic Education, 2022)
The way of Umm Abbas is the most famous path between the features of the Cairo neighborhood. It is located at the intersection of Al-Rukabiya Street and Al-Suwayfiyah Street with Al-Salifiya Street leading to Al-Qalaa Square. It is a living example that embodies the position of women and their role in charitable works like men. A path of imagination for his mother to set a path that has become one of the most famous sables in Egypt, a rare heritage building, decorated with bright colors and impressive artistic inscriptions, and the main purpose of it was to distribute clean drinking water to passers-by for reward and supplication, as it was attached to it by a book and teachers In order to teach children science as is the case in public schools that were established during the era of Khedive Ismail.